DIVERSITY IN MARKET CHANGE: EXPLORATORY RESEARCH ON THE FLAT-PANEL TV MARKET - Marina Imai; Nozomu Imai (PEOPLE: International Journal of Social Sciences, 2025)
The main focus of this study is to clarify the differences in how markets are formed and changed in two markets where overlapping companies operate using same technologies. Drawing on insights from market category research, the following points are noted: (1) Market categories are embedded within broader social classification systems, which vary by society and culture, (2) when market categories are formed, they are shaped in relation to existing market categories, meaning that the characteristics of existing categories influence the creation of new ones. However, there have been few comparative studies of markets in different regions for products that use similar technology. In this study, we compared the market change process in the flat-panel TV markets of Japan and North America through content analysis of press releases published by companies.The comparative analysis revealed that the way in which market categories change differs between the flat-panel TV markets of Japan and North America. In terms of products, both the Japanese and North American markets saw a similar proportion of flat-panel TVs that could be used to access content and applications over the internet. In the North American market, a new category label was used for these flat-panel TVs with new functions, and a new market category was formed. In contrast, no new TV category was formed in the Japanese market. In the Japanese market, these TV was not introduced as a new type of TV, but as a conventional flat-panel TV with new functions added.